On reality of human body - Płoszczyniec, Antoni (Hybris, 2016)
“Body” is here understood prima facie as biological, organic body (Körper). This article claims, that ignoring this aspect of human being is wrong, because many important anthropological and existential phenomena are based on reality of Körper, not only Leib. “Reality” of human body is understood as a constitutive element of a human being’s essence, without which one cannot be a human. First were presented Heidegger’s critique of philosophical anthropology and concept of animalitas. According to the author of Being and Time, referring to biological corporeality is secondary to fundamental ontology. This article criticizes Heidegger and claims, that many phenomena indicated by him are primary understandable only by paying attention to organic dimension of human body, dimension underestimated by Heidegger. Then, a number of „existentialist” aspects of human life were presented, and their consideration confirms that it is impossible to gain insight on a human if his corporeal dimension is ignored.